Water Quality Mapping of Piped Water Supply in Malang City - Indonesia - Rofida, Rona (International Journal of Integrated Engineering, 2019)
PDAM Tirta Dharma of Malang City is probably the only water supply company (PDAM) in Indonesia which distributes drinking water to its customers at city wide. The PDAM is easily entitled to distribute drinking water as the raw water is originated from springs and groundwater with high quality of raw water supply. Raw water is simply chlorinated prior to distribution which then water must have residual chlorine of at least 0.2 mg/L, no total coliform, and minimum pressure heads of 1 bar at any house connection of the customers. PDAM Malang has 85 district meter areas (DMA) which covers 85% of Malang City in 2018. This study is aimed to assess public water service in Malang City regarding residual chlorine, total coliform, and residual heads at selected house connections which the results are then plotted using open source software of ArcGIS 10.3. Out of 85 DMA, 58 areas were able to distribute drinking water in accordance with Indonesia Drinking Water Standard. Out of 85 selected sampling points for the three water services, 68% showed that the water quality complied with Indonesia Standard.